Review of Distribution Network Collaborated Control-Protection Technologies Under High Proportion of New Energy Integration - QIN Wenping; WEI Qi; CAI Yitian; HAN Xiaoqing; YAN Zheng; ZHAO Kai (Taiyuan Ligong Daxue xuebao)
[Purposes] The high proportion of new energy connected to power grid through power electronic devices seriously affects the safe and stable operation of power system distribution network, and further strengthens the requirements for relay protection. The proposed collaborated control-protection technology is of great significance for the new power system, but the research in this area is relatively still limited. [Methods] First, the development and application of new energy grid-connected converters were summarized. Second, the basic principle and research status of collaborated control-protection technology were introduced. Finally, the collaborated control-protection methods in the distribution network after the high proportion of new energy being connected to the grid were summarized, and the future research direction and emphases of collaborated control-protection method in new power system distribution network were put forward. [Conclusions] This review provides comprehensive academic materials for relevant scholars and enterprises.